Exosomes in the Pathogenesis, Progression, and Treatment of Osteoarthritis - Yishu Fan; Zhong Li; Yuchen He (Bioengineering, 2022)
Osteoarthritis (OA) is a prevalent and debilitating age-related joint disease characterized by articular cartilage degeneration, synovial membrane inflammation, osteophyte formation, as well as subchondral bone sclerosis. OA drugs at present are mainly palliative and do not halt or reverse disease progression. Currently, no disease-modifying OA drugs (DMOADs) are available and total joint arthroplasty remains a last resort. Therefore, there is an urgent need for the development of efficacious treatments for OA management. Among all novel pharmaco-therapeutical options, exosome-based therapeutic strategies are highly promising. Exosome cargoes, which include proteins, lipids, cytokines, and various RNA subtypes, are potentially capable of regulating intercellular communications and gene expression in target cells and tissues involved in OA development. With extensive research in recent years, exosomes in OA studies are no longer limited to classic, mesenchymal stem cell (MSC)-derived vesicles. New origins, structures, and functions of exosomes are constantly being discovered and investigated. This review systematically summarizes the non-classic origins, biosynthesis, and extraction of exosomes, describes modification and delivery techniques, explores their role in OA pathogenesis and progression, and discusses their therapeutic potential and hurdles to overcome in OA treatment.